Measuring whole-body volatile organic compound emission by humans: A pilot study using an air-tight environmental chamber. (15th April 2019) - He, Junzhou; Zou, Ziwei; Yang, Xudong
Abstract: Volatile organic compounds (VOCs) emitted from the human body are an important source of bioeffluents to indoor environments. A mid-sized (2 m × 2 m × 2 m), air-tight environmental chamber was used to measure VOC emissions from the whole body of each participant. Air tightness, homogeneity, adsorption, and desorption were controlled to satisfy the requirements of the experiment. Background concentrations of VOCs and ozone were maintained at a low level. To estimate human emission rates, the VOC concentrations of the chamber's air and of exhaled breath were collected by Tenax-TA tubes and analyzed through gas chromatography-mass spectrometry. Fourteen healthy participants enrolled in the pilot experiment. The chemical components of volatile emissions from the breath and the whole body of participants were found to be similar. The average emission rate of total VOC (TVOC) from the whole-body was 742.8 μg/h (SD = 464.7 μg/h), while the average TVOC emission rate from the breath samples was 41.4 μg/h (SD = 11.7 μg/h). In addition, the VOCs detected in the whole-body analyses were mainly alkanes with 3–6 carbons, while the VOCs detected in the breath sample analyses were primarily acetone and isoprene. In comparison with previous studies, the detected VOC types were mostly consistent, but the specific compounds varied. Moreover, the emission rates of very volatile organic compounds (VVOCs) were lower in this study, whereas the aromatics were on the same order of magnitude. Highlights: An air-tight environmental chamber was used to obtain VOC emissions from the whole body of an individual person. The VOCs detected in the whole-body sample of the 14 healthy college students were dominated by alkanes with 3–6 carbons. The emissions of aromatics were within the same order of magnitude as previous studies, whereas VVOCs were lower.